2016
DOI: 10.16970/ted.56436
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of entomopathogenic fungi on insect pests of stored wheat and maize in Central and South Anatolia in Turkey

Abstract: SummaryNaturally occurring fungal pathogens of stored-grain insect pests were identified and quantified using different insect sampling techniques in wheat and maize storage facilities in Central and South Anatolia in Turkey. Storage facilities were sampled by probing, trapping and visual inspection in five cities (Şanlıurfa, Kahramanmaraş, Adana, Mersin and Konya) from June to November 2013. Entomopathogenic fungi recovered from dead insects were identified to species level by sequencing the ITS1-5.8S-ITS2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Distribution in World: Widely distributed (Halstead, 1993) Distribution in Turkey: Adana, Ankara, Konya, Mersin, Şanlıurfa (Bağcı et. al., 2014;Er et. al., 2016) .…”
Section: Resultsmentioning
confidence: 99%
“…Distribution in World: Widely distributed (Halstead, 1993) Distribution in Turkey: Adana, Ankara, Konya, Mersin, Şanlıurfa (Bağcı et. al., 2014;Er et. al., 2016) .…”
Section: Resultsmentioning
confidence: 99%
“…Although some previous studies have demonstrated the occurrence of EPF on insect pests of stored-grains and their by-products (Odour et al, 2000;Mar et al, 2012;Barra et al, 2013;Er et al, 2016;Batta and Kavallieratos, 2018), as far as we know, no commercial biopesticides based on EPF bio-agents are registered for use against the stored-product insect pests. Also, there is no integration of any effective strain (formulated or unformulated) of EPF in the management of stored-product insects.…”
Section: Discussionmentioning
confidence: 96%
“…ARDRA classifies analysis of BCAs and method procedure, helped us get distinctive hereditary foundation and lessen outstanding task at hand by abstaining from utilizing BCAs of same species in our examination. In some applicable research, order strategies based on genetic background were not been concerned well [7], which brought about duplication of same species and time-consuming.…”
Section: Discussionmentioning
confidence: 99%